Coal forming environment and coal accumulation law of Upper Paleozoic in Huanghua Depression. Issue 1 (November 2020) - Li, Chuanming; Zhao, Changyi; Li, Hongjun; Liu, Haitao; Zhang, Hong; Cui, Yu; Yang, Runze
Abstract: The characteristics of sequence stratigraphy, geochemistry and coal petrology of Taiyuan and Shanxi formations of Upper Paleozoic in Huanghua depression are systematically analyzed in this paper, It is considered that the thick coal seams in the study area are formed near the transgressive surface, while the coal seams formed at the most flooding surface are not so thick. The thick coal seams are mostly formed in the transgressive system tract, and the coal seams in the highstand system tract are relatively thin, and the coal seams in the lowstand system tract are hardly developed. There are mainly three coal forming models in the study area: ① the land surface coastal coal forming model; ② the abandoned clastic system tract coal forming model; ③ the shallow water delta coal forming model. The main coal forming model is the epicontinental seashore coal forming mode, and the Taiyuan Formation thick coal seam is mainly formed in the epicontinental seashore coal forming mode, and the Shanxi Formation thick coal seam is mainly formed in the waste clastic coal forming mode.